TRPC1 channels underlie stretch-modulated sarcoplasmic reticulum calcium leak in cardiomyocytes - Streiff, Molly E.; Corbin, Andrea C.; Ahmad, Azmi A.; Hunter, Chris; Sachse, Frank B. (Frontiers in Physiology, 2022)
Transient receptor potential canonical 1 (TRPC1) channels are Ca2+-permeable ion channels expressed in cardiomyocytes. An involvement of TRPC1 channels in cardiac diseases is widely established. However, the physiological role of TRPC1 channels and their contribution to disease development are still under investigation. Our prior work suggested that TRPC1 forms Ca2+ leak channels located in the sarcoplasmic reticulum (SR) membrane. Prior studies suggested that TRPC1 channels in the cell membrane are mechanosensitive, but this was not yet investigated in cardiomyocytes or for SR localized TRPC1 channels. We applied adenoviral transfection to overexpress or suppress TRPC1 expression in neonatal rat ventricular myocytes (NRVMs). Transfections were evaluated with RT-qPCR, western blot, and fluorescent imaging. Single-molecule localization microscopy revealed high colocalization of exogenously expressed TRPC1 and the sarco/endoplasmic reticulum Ca2+ ATPase (SERCA2). To test our hypothesis that TRPC1 channels contribute to mechanosensitive Ca2+ SR leak, we directly measured SR Ca2+ concentration ([Ca2+]SR) using adenoviral transfection with a novel ratiometric genetically encoded SR-targeting Ca2+ sensor. We performed fluorescence imaging to quantitatively assess [Ca2+]SR and leak through TRPC1 channels of NRVMs cultured on stretchable silicone membranes. [Ca2+]SR was increased in cells with suppressed TRPC1 expression vs. control and TRPC1-overexpressing cells. We also detected a significant reduction in [Ca2+]SR in cells with TRPC1 overexpression when 10% uniaxial stretch was applied. These findings indicate that TRPC1 channels underlie the mechanosensitive modulation of [Ca2+]SR. Our findings are critical for understanding the physiological role of TRPC1 channels and support the development of pharmacological therapies for cardiac diseases.